The Present in Delhi's pasts - Sunil Kumar (New Delhi, 2002)
The essays in this volume are about old monuments and villages in New Delhi. The author investigates both, the medieval history of these sites and changes that have occured in these areas in more recent times. Relying upon Persian documentation and field-work, the author narrates the histories of these sites over the last millennium. It is a history of how, ever so gradually, the present has erased and rewritten the past of New Delhi. Contents: Preface to the Second Edition and Introduction 1. Qutb and Modern Memory 2 A Medieval Reservoir and Modern Urban Planning: Local Society and the Hauz-i Rani 3. Making Sacred History, or Everyone his/her own Historian: The Pasts of the Village of Saidlajab 4. Naming 5. Reflections on the Past and Present of Two Sufi Dargahs in Delhi.
Keywords: Unbanisation